Analysis of the Performance Measurement Models According to the Requirements of the Procurement Business Process - Komatina, Nikola; Nestić, Snežana; Aleksić, Aleksandar (International Journal of Industrial Engineering and Management, 2019)
The customer needs shape business activities continuously so the need for improving effectiveness stands as mandatory for overall business success. This paper analyses existing models for measuring the business processes performance from the aspect of their applicability to the procurement process. The paper first explains the concepts of enterprise performance, business process performance, and key performance indicators. Subsequently, a literature review of the identification problem of procurement process performance and key performance indicators is given. The models discussed and explained in this paper are Balanced Scorecard, SCOR model, performance measurement matrix, ABC model, and DOE/NV model. The model comparison was based on several relevant criteria. Article history: Received (04-SEP-2019); Revised (01-JUN-2019); Accepted (17-JUN-2019); Published online (2-JUL-2019)